Diversity of Bacillus megaterium isolates cultured from honeys - López, Ana C. (2009)
Bacillus megaterium isolates recovered from Argentinean honeys (n ¼ 48) were compared with isolates recovered from honey from other countries (n ¼ 4) and with strain NRRL B-939. All the isolates and the NRRL strain were characterized using rep-PCR fingerprinting with primers BOX-, REP- and ERIC-; restriction fragment length polymorphism analysis of a 16S rRNA gene fragment (16S rRNA PCR/RFLP), and morphological and biochemical tests. There was a high degree of diversity, both phenotypic and genotypic among the isolates of B. megaterium. Our results not only show considerable levels of diversity among isolates of B. megaterium analyzed here but also that repetitive sequences such as BOX, ERIC and REP are reliable tools to characterize isolates at the genomic level. Haemolytic activity was shown by 77% of the isolates, as b-haemolysis (40 isolates) or a-haemolysis (one isolate). Within the b-haemolytic group, 10% of isolates produced a discontinuous haemolytic pattern, which is usually correlated with enterotoxin activity in other bacterial species. In addition, coagulase activity was detected in 74% of 53 isolates tested suggesting a pathogenic activity not ordinarily reported as a property of B. megaterium. According to our knowledge, this is the first report of phenotypic and genotypic characterization of B. megaterium isolates from honey.